2020
DOI: 10.1002/ppul.24895
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 cardiac involvement in a 38‐day old infant

Abstract: The spectrum of clinical manifestations of coronavirus disease 2019 in children is yet to be fully elucidated. We report the case of an infant who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and developed mild cardiovascular inflammation, a novelty for patients of very young age, that contributes to defining the puzzling nature of this disease in pediatric patients. The potential cardiovascular involvement of SARS‐CoV‐2 in children should always be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The characteristics and demographic features of the total of 45 COVID-19 patients with CI included in the selected case reports and case series are demonstrated in supplementary table 3 [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Patients' age ranged from 38 days to 74 years and approximately 62% of them were males.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics and demographic features of the total of 45 COVID-19 patients with CI included in the selected case reports and case series are demonstrated in supplementary table 3 [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. Patients' age ranged from 38 days to 74 years and approximately 62% of them were males.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports/series gave a better insight into the associated factors with CI in each individual. In this review, 11 case studies showed that 78% of COVID-19 patients with CI, were children/adolescentshad none of them had any underlying CVD [ 20 , 21 , [23] , [24] , [25] , [26] , [27] , 30 , [32] , [33] , [34] ]. Furthermore, 50% of the adult COVID-19 patients who developed CI did not have any comorbid CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The infant was asymptomatic and there were no complications at birth. 62,63,[80][81][82][83][84][85][86][87] Negative cases 4,68,79,81,88-103 Mix-feeding 3 7 10 Positive cases [104][105][106] Negative cases 107 Not reported feeding practice 76 596 672 Positive cases 63,67, Negative cases 5,10,47,75,111,114,119,120,122, Positive cases 83,193,199,200 Mix-feeding 3 0 3 Positive cases 193,201 Not reported e feeding practice 125 2 127…”
Section: Participantsmentioning
confidence: 99%
“…Daniele Canarutto MD 1,2,3 Paolo Del Barba MD 1 Marianna Di Frenna MD 1 Federica Del Tedesco MD 1,2 Roberta Pajno MD 1 Maria Pia Guarneri MD 1 Graziano Barera MD 1,2 1…”
Section: Prolonged Asymptomatic Sars-cov-2 Infection In a Child Receimentioning
confidence: 99%